ISTIDRAJ PERSPEKTIF TAFSIR AL-AZHAR: RELEVANSINYA TERHADAP PERILAKU RELIGIUS GEN Z DI ERA DIGITAL - Nur Khoirunnisa Harahap; Muzakkir Muzakkir (Hikmah: Journal of Islamic Studies, 2025)
AbstractThis article examines the concept of istidraj in Hamkaâ€™s Tafsir al-Azhar and its relevance to the religious behaviour of Generation Z within digital ecosystems. Drawing on a literature-based study that employs thematic and hermeneutic analysis of Q 3:178, 6:44, and 7:182 alongside recent scholarship on digital culture, the study advances a clear novelty: an operationalised framework of istidraj indicators tailored to social-media contexts. The framework highlights indulgences that foster heedlessness, visible in binge-scrolling and the postponement of worship; the broadening of pleasures that dull ethical sensitivity, reflected in impulsive consumption and digital flexing; and an illusion of success or safety from moral consequences, manifest in performative narcissism and religious overconfidence. Findings show that this mapping functions as a theological evaluation tool for diagnosing erosions of piety online while also guiding educational interventions. Practical implications include integrating verse-based digital-ethical literacy modules into Islamic Education courses, designing campus daâ€˜wah content such as short videos and podcasts that internalises the signs of istidraj, and employing a digital self-accountability rubric for student mentorship. The study is limited by its non-empirical scope and reliance on a single tafsÄ«r corpus, which precludes direct behavioural measurement. Future work should involve field research through surveys or in-depth interviews, the development of a psychometric scale for istidraj indicators, and experimental tests of digital daâ€˜wah materials built on this framework.Â AbstrakPenelitian ini menganalisis konsep istidraj dalam Tafsir Al-Azhar karya Buya Hamka dan relevansinya terhadap perilaku religius Generasi Z di ekosistem digital. Berbasis studi pustaka dengan analisis tematikâ€“hermeneutik atas QS Ä€li â€˜ImrÄn 3:178, Al-Anâ€˜Äm 6:44, dan Al-Aâ€˜rÄf 7:182 beserta literatur mutakhir tentang budaya digital, penelitian ini menonjolkan kebaruan berupa kerangka indikator istidraj yang teroperasionalisasi untuk konteks media sosial. Kerangka tersebut ditandai oleh pembiaran kenikmatan yang melalaikan yang tampak pada binge-scrolling dan penundaan ibadah, pelapangan kesenangan yang menumpulkan kepekaan etis yang tercermin dalam impuls konsumsi dan praktik flexing digital, serta ilusi keberhasilan atau rasa aman dari konsekuensi moral yang hadir sebagai narsisme performatif dan overconfidence religius. Temuan memperlihatkan bahwa pemetaan ini efektif sebagai alat evaluasi teologis untuk membaca degradasi kesalehan di ruang daring sekaligus memandu intervensi pendidikan. Implikasi praktis meliputi integrasi modul literasi digital-etis berbasis ayat dalam pembelajaran PAI, perancangan konten dakwah kampus seperti video pendek dan podcast yang menginternalisasikan tanda-tanda istidraj, serta penggunaan rubrik muhasabah digital untuk pembinaan mahasiswa. Penelitian ini terbatas pada pendekatan non-empirik dan fokus pada satu korpus tafsir, sehingga belum mengukur perilaku secara langsung. Ke depan, disarankan studi lapangan melalui survei atau wawancara mendalam, pengembangan skala psikometrik indikator istidraj, dan uji coba efektivitas materi dakwah digital yang dibangun dari kerangka ini.Â